Enabling the Just Energy Transition in South Africa - Wolf, Victoria (Department of Political Studies, 2024)
South Africa's recently published Just Transition Framework (2022) signalled a critical juncture for the country's heretofore separate energy decarbonisation and developmental agendas. However, despite the win-win framing of the South African just energy transition, evidence suggests that it may do little to mitigate socio-economic and environmental inequality, necessitating new approaches to energy scholarship and policy planning. To date, the traditional principle of distributive justice (i.e. ensuring equitable access to energy) has been at the forefront of South Africa's approach to energy planning given the country's highly unequal socio-economic profile. Restorative energy justice, however, is increasingly being recognised across just energy transition research and practice as a means to both address and redress systemic inequalities within energy systems and importantly, to identify practical policy pathways – particularly in the varied and unique contexts of the Global South. In this light, this study provides a critical review of the state of the South African just energy transition with a focus on the potential of restorative energy justice in particular to enhance socio-economic inclusion, as opposed to the retributive or corrective approaches of distributive and procedural justice (McCauley and Heffron, 2017:2). By examining the South African just energy transition across market, social/environmental, and public/political dimensions, this study finds that while the just energy transition is distinctly an integrative framework, restorative energy justice is inadequately represented within the country's energy political economy. Ultimately, it is suggested that restorative policy instruments such as local content and ownership requirements, environmental impact assessments, environmental tax and energy financial reserve obligations serve as valuable conceptual bridges between scholarship and practice.